'Get an early check – Chrysanthemum tea': An outcome evaluation of a multimedia campaign promoting HIV testing among men who have sex with men in Hong Kong. Issue 5 (24th January 2018) - Kwan, NNM; Wong, AMH; Fang, Y; Wang, Z
Abstract : Objectives: 'Get an early check – chrysanthemum tea' was a multimedia campaign promoting HIV testing targeting Chinese‐speaking men who have sex with men (MSM) in Hong Kong, China. It ran from October to December 2015. This study was carried out to investigate the level of campaign exposure among Chinese‐speaking MSM in Hong Kong and the association between uptake of HIV testing in the last 6 months and campaign exposure. Methods: A cross‐sectional survey was conducted 6 months after the campaign was launched. Participants were Hong Kong Chinese‐speaking men aged ≥18 years who had had anal or oral sex with at least one man in their lifetime. A total of 153 eligible participants completed the anonymous self‐administered questionnaire. Results: Among the participants, 45.8% had been exposed to the campaign and 43.1% had taken up HIV testing in the last 6 months. In multivariate logistic regression analysis, exposure to the campaign [multivariate odds ratio (ORm) 2.55; 95% confidence interval (CI) 1.25, 5.19] and having had anal intercourse with a nonregular sex partner (ORm 2.36; 95% CI 1.05, 5.31) in the last 6 months were significantly associated with uptake of HIV testing in the last 6 months. Conclusions: The campaign had relatively good reach in the target population and may have been useful to encourage them to take up HIV testing. Future campaigns promoting HIV testing among MSM in Hong Kong are still needed. Such programmes should consider making use of viral videos, having a longer project duration and developing culturally sensitive materials for non‐Chinese‐speaking MSM.